2010
DOI: 10.1097/cmr.0b013e32833bd89e
|View full text |Cite
|
Sign up to set email alerts
|

The immunohistochemistry of invasive and proliferative phenotype switching in melanoma: a case report

Abstract: Purpose To date there remains no effective therapy for metastatic melanoma and at the molecular level disease progression remains poorly understood. Recent work by our group led to the development of a novel phenotype switching model for melanoma progression, wherein cells transition back-and-forth between states of proliferation and invasion to drive disease progression. To explore the model’s clinical relevance we interrogated phenotype-specific expression patterns in human melanoma patient material. Exper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
43
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(50 citation statements)
references
References 22 publications
6
43
0
1
Order By: Relevance
“…However, further studies, with a larger number of samples, are needed to assess the extent to which this phenomenon exists. Note that in agreement with this result, it has been reported that MITF showed a consistent anti-correlation with Glut1, a hypoxia marker, and a HIF1a target gene (Eichhoff et al, 2010).…”
Section: Discussionsupporting
confidence: 78%
“…However, further studies, with a larger number of samples, are needed to assess the extent to which this phenomenon exists. Note that in agreement with this result, it has been reported that MITF showed a consistent anti-correlation with Glut1, a hypoxia marker, and a HIF1a target gene (Eichhoff et al, 2010).…”
Section: Discussionsupporting
confidence: 78%
“…This included Wnt5a, which had previously been implicated in melanoma metastasis (10,11). Other studies have confirmed that melanoma cell lines segregate into these distinct expression clusters (12,13).…”
Section: Reactivation Of the Mapk Pathway Confers Resistance To Targementioning
confidence: 99%
“…Specifically, whereas melanoma cells in the primary tumor as well as the secondary metastatic tumor were shown to have a phenotype defined by low levels of the transcription factor Brn-2 and a high level of pigmentation, highly motile, actively metastasizing melanoma cells were shown to express a predominantly Brn-2-high/pigment-low phenotype (Pinner et al, 2009). In a patient-matched analysis of both a primary metastatic lesion and distant metastases, Eichhoff et al demonstrated that, consistent with our description of proliferative and invasive melanoma phenotypes, cells in the primary and distant tumors expressed high levels of MITF and Melan-A, while cells in the "unstructured" regions of these tumors (areas from which metastatic cells are most likely to be derived) stained heavily for WNT5A and far less for Mitf and Melan-A (Eichhoff et al, 2010). Strikingly, this study also revealed latestage metastatic melanoma cells adopted phenotypes and morphologies nearly identical to early-phase cells, indicating that melanoma cells have significant plasticity with regards to their gene expression profile (Eichhoff et al, 2010).…”
Section: Phenotype Switching and Tumor Heterogeneitymentioning
confidence: 54%
“…In a patient-matched analysis of both a primary metastatic lesion and distant metastases, Eichhoff et al demonstrated that, consistent with our description of proliferative and invasive melanoma phenotypes, cells in the primary and distant tumors expressed high levels of MITF and Melan-A, while cells in the "unstructured" regions of these tumors (areas from which metastatic cells are most likely to be derived) stained heavily for WNT5A and far less for Mitf and Melan-A (Eichhoff et al, 2010). Strikingly, this study also revealed latestage metastatic melanoma cells adopted phenotypes and morphologies nearly identical to early-phase cells, indicating that melanoma cells have significant plasticity with regards to their gene expression profile (Eichhoff et al, 2010). Lending further support to the existence of phenotype switching are the findings of Hoek et al, in which seed melanoma cells of either an exclusively proliferative or exclusively invasive phenotype were injected subcutaneously into immunocompromised mice (Hoek et al, 2008).…”
Section: Phenotype Switching and Tumor Heterogeneitymentioning
confidence: 54%
See 1 more Smart Citation